Psychological resources and strategies to cope with stress at work (2017)
Introduction: the choice of strategies to cope with stress has differential effects on individual and organizationaloutcomes (e.g. well-being and performance at work). This study examined to what extent individuals differing intheir positive psychological resources (optimism, hope, self-efficacy and resilience) implement different strategiesto cope with stress in terms of change, acceptance, or withdrawal from a source of stress in an organizationalsetting.Method: A questionnaire was filled out by 554 employees from different organizations representing a wide rangeof jobs and positions.Results: Structural Equation Modeling (SEM; c2(7) = 27:64, p < :01, GFI = :99, NFI = :91, CFI = :93,RMSEA = :07)Conclusion: the results indicated that psychological resources (optimism, hope, self-efficacy and resilience) werepositively related to coping by change and by acceptance and negatively related to withdrawal. The theoreticalimplications are discussed.